(untitled) (Journal of Laboratory Animal Science, 2018)
Studies were carried out to evaluate the effect of dietary supplementation of curcumin on toxicopathology of aflatoxicosis in laboratory mouse following short-term exposure to aflatoxin B1. Sexually matured Swiss albino mice of either sex weighing between 28-30g were divided into two groups consisting of six animals each. Animals in group I (positive control) were fed with aflatoxin B1 mixed in standard rodent chow (7.5 ppb) and group II (treatment) received aflatoxin B1 (7.5 ppb) along with curcumin (1g/kg feed) for a period of 14 days. At term, oxidative stress and hepatotoxicity were assessed by determining tissue and serum specific enzymes and by histopathology. Short term exposure to aflatoxin-B1 significantly (P< 0.05) decreased hepatic GSHr levels on account of oxidative stress as evidenced by elevated TBARS levels (group I). However, concomitant administration of curcumin has significantly (P< 0.05) reduced the TBARS and protected depletion of hepatic GSHr levels. Curcumin supplementation (group II) has markedly reduced the toxicopathological lesions in liver induced by aflatoxin B1 and consequent reduction (P< 0.05) in serum levels of both aminotransferase (s) and phosphatase. Thus, the present study demonstrated the potential benefits of dietary supplementation of curcumin in ameliorating aflatoxin induced oxidative stress in mice